Control engineering - Morris, Noel M. (New York : McGraw Hill Education, 1991)
The fourth edition of this text has been updated to accommodate the changes which have taken place in control engineering since the previous edition was published in 1983. The major development has been a rapid increase in computer control and, in particular, the introducton of programmable logic controllers. These developments are reflected in the fourth edition by the addition of a new chapter on programmable logic controllers, whilst new sections on computer control have also been added.
An Introduction to Control Engineering. Transducers. Electronic Amplifiers and Analogue Computing Techniques. Power Electronics. Frequency, Impulse, and Transient Response Testing. Stabilizing Techniques and System Performance. Electrical Machines. Digital Techniques and Digital Computer Control. Speed Control. Position Control Systems. Hydraulic Systems. Process Control. Programmable Logic Controllers. Index.
Includes bibliographical references.
Keywords: AUTOMATIC CONTROL